Fossil Encope (Echinoidea) from the Pacific coast of southern Mexico - J. Wyatt Durham (Revista Mexicana de Ciencias Geológicas)
The only Cenozoic fossil echinoid recorded from the Pacific coast to mainland Mexico, between the Guatemalan border and Puerto Vallarta, at the entrance to the Gulf of California, is Encope micropora L. Agassiz (Palmer and Hertlein, 1936, p. 66) from the Pleistocene Colotepec Formation of the southern coast of Oaxaca (Caso, 1951, 1961; Buitrón, 1978). Recently, several Cenozoic marine basins have been discovered along the Pacific Coast (Durham et al., 1981). In two of these basins, one near La Mira, Michoacán, and the other near Santa Cruz, Oaxaca, fossil keyhold urchins (genus Encope) were found.